2017
DOI: 10.3892/mco.2017.1541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin on survival outcomes of pancreatic cancer patients with diabetes: A meta-analysis

Abstract: Abstract. Pancreatic cancer risk is reduced by metformin treatment in patients with diabetes. However, the effect of metformin on pancreatic cancer overall survival is unclear. The aim of the present study was to determine the association between metformin and clinical outcomes of pancreatic cancer patients with diabetes. An electronic and manual search was conducted using PubMed, Web of Science, Medline-Ovid and Cochrane Library databases between the beginning and March 31, 2017. A total of 8 studies consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Multiple studies have suggested that metformin use was associated with lower incidences of various solid tumours such as pancreatic, colorectal, gastric, lung and breast cancer (Gandini et al, 2014;Wang et al, 2014;Zhu et al, 2015;Shlomai et al, 2016;Kobiela et al, 2018;Li et al, 2018b). There is also accumulating evidence that supports an association of metformin use with improved outcome of several types of solid tumours (Chu et al, 2018;Hu et al, 2018;Kobiela et al, 2018;Li et al, 2018b;Tang et al, 2018;Xin et al, 2018). There are fewer studies available regarding the role of metformin in haematological malignancies.…”
mentioning
confidence: 99%
“…Multiple studies have suggested that metformin use was associated with lower incidences of various solid tumours such as pancreatic, colorectal, gastric, lung and breast cancer (Gandini et al, 2014;Wang et al, 2014;Zhu et al, 2015;Shlomai et al, 2016;Kobiela et al, 2018;Li et al, 2018b). There is also accumulating evidence that supports an association of metformin use with improved outcome of several types of solid tumours (Chu et al, 2018;Hu et al, 2018;Kobiela et al, 2018;Li et al, 2018b;Tang et al, 2018;Xin et al, 2018). There are fewer studies available regarding the role of metformin in haematological malignancies.…”
mentioning
confidence: 99%
“…In contrast, the same study found that the use of sulphonylureas or insulin was associated with 1.49‐ (95% CI: 1.00‐2.23) and 2.58‐fold (95% CI: 1.72‐3.90) higher risks of breast cancer death. Other recent meta‐analyses have also reported a beneficial effect of metformin on incidence and/or survival in various cancers including liver, prostate cancer, colorectal cancer, endometrial cancer and pancreatic cancer …”
Section: Resultsmentioning
confidence: 99%
“…Other recent meta-analyses have also reported a beneficial effect of metformin on incidence and/or survival in various cancers including liver, 54,55 prostate cancer, 56 colorectal cancer, 57,58 endometrial cancer 59,60 and pancreatic cancer. 61 Although some observational studies show clear evidence of survival benefit in cancer patients with diabetes receiving metformin, the situation is by no means clear. The complexity of the available evidence is illustrated by observational studies with negative findings.…”
Section: Potential Use In Oncologymentioning
confidence: 99%
“…The anti-tumorigenic properties of MET have been reported in several studies associated with indirect action (reduced insulin levels) or direct actions on molecular pathways that regulate breast tumor cell growth and death (36). MET may mediate its effects through actions on different cells of the tumor microenvironment, including MOs-macrophages that would be involved in controlling tumor cell growth and progression.…”
Section: Discussionmentioning
confidence: 99%